Soft magnetic metal powder having high spheroidization rate and method for producing same
By using a phosphorus-based reducing agent in the liquid phase reduction method and spherical treatment, soft magnetic metal powder with narrow particle size distribution and high spherical rate was prepared, which solved the problem of difficult to take into account both magnetic characteristics and surface smoothness in the prior art, and achieved the effect of high magnetic characteristics and excellent surface smoothness.
Patent Information
- Application Number
- CN202380062624.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-08-28
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to produce soft magnetic metal powder with narrow particle size distribution while maintaining excellent magnetic properties, resulting in poor surface smoothness when thinning, and a high content of B will reduce magnetic properties.
By using a phosphorus-based reducing agent in the liquid phase reduction method and subsequently undergoing spherification treatment, soft magnetic metal powder with an average particle size of 0.05 μm to 1.5 μm, a change coefficient of 0.25 or less and a spherification rate of 75% was prepared to ensure that the content of B was less than 1.5%.
It realizes soft magnetic metal powder with narrow particle size distribution and excellent surface smoothness, which can effectively suppress the reduction of magnetic characteristics caused by B, and is suitable for making electronic parts with high magnetic characteristics.
Smart Images

Figure CN119895511A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a soft magnetic metal powder. Specifically, the soft magnetic metal powder is an aggregate of fine particles, and because of its high sphericity, it can be used to prepare a slurry with low viscosity, so that it is easy to form a thin layer, and because of its small content of boron that reduces saturation magnetization, it can be used to prepare electronic parts with excellent magnetic properties, and because of its narrow particle size distribution, it has high solvent dispersibility and can form a thin layer with excellent surface smoothness. Background Art
[0002] Soft magnetic metal powders used as core materials for inductors and transformers are required to have higher densities in order to improve magnetic properties.
[0003] In addition, as electronic parts are required to be thinner, the thickness of inductors, transformers, etc. is being reduced.
[0004] As a method for producing soft magnetic metal powder, water atomization, gas atomization, spray pyrolysis, etc. are generally used. However, the particle size distribution of soft magnetic metal powder produced by these methods becomes wide.
[0005] If the particle size distribution is wide, there is a problem that it is difficult to obtain good surface smoothness when the layer is thinned.
[0006] As described in Patent Document 1 mentioned later, fine soft magnetic metal powder can be produced by a liquid phase reduction method in which a metal salt aqueous solution is reduced with a boron (B)-based reducing agent. However, when a B-based reducing agent is used, there is a problem that the magnetic properties are reduced due to the influence of B.
[0007] Therefore, there is a demand for the development of a soft magnetic metal powder having a narrow particle size distribution, excellent surface smoothness when thinned, and a low B content and capable of producing electronic parts having excellent magnetic properties.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent document 1: Japanese Patent Application Laid-Open No. 2010-261065.
[0011] Non-patent literature
[0012] Non-patent document 1: Materials Chemistry and Physics 123 (2010) 487-493. Summary of the invention
[0013] Problems to be solved by the invention
[0014] Patent document 1 describes a method for producing soft magnetic metal powder with a smaller particle size than before by a liquid phase reduction method, in which a reducing solution containing a B-based reducing agent is dripped into an aqueous iron salt solution containing an iron salt, a complexing agent, a dispersant, a pH adjuster, and a P-based reducing agent.
[0015] However, in the case of the liquid phase reduction method described in Patent Document 1, when the B amount is reduced in order to improve the magnetic properties, a single-phase α-Fe particle powder is obtained, which becomes particles with a low sphericity in the crystal structure, and the filling property of the coating film deteriorates, so there is a problem that a smooth thin layer cannot be obtained.
[0016] Non-Patent Document 1 discloses a technique using a polyol method as a method for synthesizing α-Fe particle powder.
[0017] However, the production method described in Non-Patent Document 1 has a problem that the spheroidization rate is low and that the resulting particles are aggregates of particles having a wide particle size distribution, so that a thin layer having excellent surface smoothness cannot be obtained.
[0018] The inventors of the present invention took solving the above-mentioned problems as a technical task and repeatedly carried out multiple tentative trials and experiments. As a result, they successfully produced the following soft magnetic metal powder, thereby solving the above-mentioned problems: the average particle size is greater than 0.05μm and less than 1.5μm, the coefficient of variation expressed by [standard deviation of particle size / average particle size] is less than 0.25, the B content is less than 1.5% by weight (excluding 0), and the sphericity rate expressed by [(area / area of the smallest circumscribed circle)×100] is greater than 75%.
[0019] The soft magnetic metal powder of the present invention is a fine particle with a small average particle size, and because of its high spheroidization rate, it is possible to prepare a slurry with low viscosity, so that it is easy to form a thin layer. In addition, because the content of B that reduces saturation magnetization is low, it is possible to suppress the reduction of magnetic properties due to B, so that electronic parts with excellent magnetic properties can be produced, and because of its narrow particle size distribution, it is possible to form a thin layer with excellent surface smoothness because of its high solvent dispersibility.
[0020] Technical solutions to solve problems
[0021] The above technical problems can be solved by the following present invention.
[0022] The present invention is a soft magnetic metal powder having an average particle size of greater than 0.05 μm and less than 1.5 μm, a coefficient of variation expressed by the following (Formula 1) of less than 0.25, a boron content of less than 1.5 weight % (excluding 0), and a spheroidization rate expressed by the following (Formula 2) of more than 75%.
[0023] (Formula 1) Standard deviation of particle size / average particle size
[0024] (Formula 2) (Area / Area of the smallest circumscribed circle) × 100
[0025] Furthermore, the present invention provides the soft magnetic metal powder having an oxygen content of 3.0 wt % or less.
[0026] Furthermore, the present invention provides the soft magnetic metal powder having an iron content of 93% by weight or more.
[0027] In addition, the present invention provides the soft magnetic metal powder coated with one or two or more metal oxides.
[0028] In addition, the present invention is the soft magnetic metal powder wherein the metal element of the metal oxide is aluminum, silicon, zirconium, titanium, yttrium or phosphorus.
[0029] In addition, the present invention is a method for manufacturing the soft magnetic metal powder, wherein the soft magnetic metal powder is obtained by spheroidizing the soft magnetic metal powder manufactured by a liquid phase reduction method, and the liquid phase reduction method is to drop a reducing agent containing a boron-based reducing agent into a metal salt aqueous solution containing a metal salt, a complexing agent, a pH adjuster, and a phosphorus-based reducing agent.
[0030] In addition, the present invention is a method for producing the soft magnetic metal powder, wherein the soft magnetic metal powder is obtained by spheroidizing the soft magnetic metal powder through a mechanochemical treatment.
[0031] Effects of the Invention
[0032] The present invention provides a soft magnetic metal powder which is an aggregate of fine particles having an average particle size of 0.05 μm to 1.5 μm, and thus has improved filling properties or dispersibility in a solvent such as a resin, and can produce electronic parts with high magnetic properties.
[0033] Furthermore, since the particle size distribution of the aggregate is narrow such that the coefficient of variation expressed by (Formula 1) is 0.25 or less, the dispersion property in a solvent is high, and a thin layer having excellent surface smoothness can be formed.
[0034] In addition, since the content of B which reduces saturation magnetization is less than 1.5 wt % (excluding 0), the reduction in magnetic properties due to B can be suppressed, and thus the soft magnetic metal powder can be used to produce electronic components with excellent magnetic properties.
[0035] In addition, since the spheroidization rate represented by (Formula 2) is as high as 75% or more, the filling or dispersibility into solvents such as resins is improved, so the viscosity when forming a slurry becomes lower. Therefore, it is a soft magnetic metal powder that is easy to form a thin layer, and the formed thin layer becomes a thin layer with excellent surface smoothness.
[0036] Furthermore, when the content of oxygen (O) is 3.0 wt % or less, a decrease in saturation magnetization due to the oxide film can be suppressed.
[0037] When the content of iron (Fe) is 93% by weight or more, a soft magnetic metal powder capable of producing electronic components having high saturation magnetization can be obtained.
[0038] Furthermore, when the soft magnetic metal powder is coated with one or more metal oxides, electrical insulation between the particles can be ensured, thereby suppressing energy loss.
[0039] The soft magnetic metal powder of the present invention can be produced by a simple method in which the soft magnetic metal powder is produced by a liquid phase reduction method using a B-based reducing agent and then subjected to spheroidization treatment.
[0040] Furthermore, if spheroidization is performed by mechanochemical treatment, a soft magnetic metal powder having a high spheroidization rate can be produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a SEM photograph of the soft magnetic metal powder of Example 1 (50,000 times).
[0042] Figure 2 This is a SEM photograph of the soft magnetic metal powder of Comparative Example 1 (50,000 times). DETAILED DESCRIPTION
[0043] The soft magnetic metal powder in the present invention is a fine particle with a high sphericity and a low boron content that reduces saturation magnetization. Therefore, it is a soft magnetic metal powder that can be used to make electronic parts with excellent magnetic properties. In addition, due to its narrow particle size distribution, it has high solvent dispersibility and can form a thin layer with excellent surface smoothness.
[0044] The average particle size of the soft magnetic metal powder in the present invention is preferably 0.05 μm to 1.5 μm, more preferably 0.07 μm to 1.0 μm, and even more preferably 0.1 μm to 0.8 μm.
[0045] This is because when the average particle size is less than 0.05 μm, the ratio of the oxide film on the particle surface increases, so the saturation magnetization decreases. When it exceeds 1.5 μm, the maximum height (Rmax) of the thin layer surface increases, and the smoothness may decrease.
[0046] The average particle size can be calculated by measuring the longest diameters of all particles within a field of view of an image captured at 2000 to 10000 times using a scanning electron microscope (SEM) using image analysis software and averaging the measured diameters.
[0047] The coefficient of variation of the soft magnetic metal powder in the present invention is preferably 0.25 or less, more preferably 0.24 or less, and even more preferably 0.22 or less.
[0048] This is because when the coefficient of variation exceeds 0.25, the value of Rmax becomes high, and the smoothness of the thin layer surface may be reduced.
[0049] The coefficient of variation can be calculated by the following (Formula 1).
[0050] (Formula 1) Standard deviation of particle size / average particle size
[0051] In addition, the lower limit of the coefficient of variation is approximately 0.001.
[0052] The spheroidization rate of the soft magnetic metal powder of the present invention is preferably 75% or more, more preferably 78% or more, and even more preferably 79% or more.
[0053] This is because the higher the spheroidization rate, the lower the viscosity of the slurry dispersed in a solvent such as a resin, and the lower the Rmax value of the thin layer surface.
[0054] When the spheroidization rate of the soft magnetic metal powder is less than 75%, the viscosity of the slurry when dispersed in the resin becomes high, and the Rmax value of the thin layer surface becomes high.
[0055] The sphericity can be calculated by the following (Formula 2) by measuring the area of all particles and the area of the minimum circumscribed circle in the field of view of an image captured at 2000 to 10000 times using a scanning electron microscope (SEM) using image analysis software.
[0056] (Formula 2) (Area / Area of the smallest circumscribed circle) × 100”
[0057] The content of iron (Fe) contained in the soft magnetic metal powder of the present invention is preferably 93% by weight or more, more preferably 95% by weight or more, and even more preferably 96% by weight or more.
[0058] When the Fe content of the soft magnetic metal powder is 93% by weight or more, an electronic component having a high saturation magnetization can be produced.
[0059] Although the B content in the soft magnetic metal powder of the present invention is less than 1.5% by weight, it is not 0% by weight.
[0060] This is because, although the less B the better since it reduces the saturation magnetization, if the material is produced by a liquid phase reduction method without using a B-based reducing agent, the number of microparticles with a low spheroidization rate increases. Even if a spheroidization treatment is performed, the number of microparticles with a low spheroidization rate will increase, so the viscosity of the slurry when it is formed or the smoothness of the thin layer surface may deteriorate.
[0061] In order to suppress a decrease in saturation magnetization due to an oxide film, the content of O in the soft magnetic metal powder is preferably 3.0 wt % or less, more preferably 2.5 wt % or less, and even more preferably 2.3 wt % or less.
[0062] In addition, the lower limit of the content of O in the soft magnetic metal powder is 0.05% by weight.
[0063] The soft magnetic metal powder in the present invention may be coated with one or more metal oxides, because this is expected to improve the insulation effect.
[0064] Examples of the metal element contained in the metal oxide include aluminum (Al), silicon (Si), zirconium (Zr), titanium (Ti), yttrium (Y), and phosphorus (P).
[0065] The content of the metal element in the metal oxide is preferably 0.1% by weight to 3.0% by weight.
[0066] This is because if the content of the metal element in the metal oxide is less than 0.1% by weight, a sufficient insulating effect may not be obtained, and if it is more than 3.0% by weight, the saturation magnetization may decrease.
[0067] The soft magnetic metal powder of the present invention may contain P, but it is not essential.
[0068] The P content of the soft magnetic metal powder of the present invention is preferably 2.0 wt % or less, more preferably 1.0 wt % or less, and even more preferably 0.5 wt % or less.
[0069] When the content of P exceeds 2.0 wt %, the ratio of the non-magnetic component increases, so the saturation magnetization decreases, and there is a possibility that sufficient magnetic properties cannot be obtained.
[0070] The viscosity of the dispersion containing the soft magnetic metal powder in the present invention, that is, the slurry, is preferably 50 Pa·s or less, and more preferably 45 Pa·s or less.
[0071] The maximum height (Rmax) of a thin layer (film thickness 10 μm to 30 μm) using the soft magnetic metal powder slurry of the present invention is preferably less than 3.5 μm, more preferably 3.0 μm or less.
[0072] When the maximum height (Rmax) of a thin layer (film thickness 10 μm to 30 μm) using a soft magnetic metal powder slurry is 3.5 μm or more, it is difficult to maintain the smoothness of the thin layer surface.
[0073] When manufacturing electronic components having sufficient magnetic properties, the saturation magnetization of the soft magnetic metal powder is preferably 190 Wb·m / kg or more, and the coercive force is preferably 10 kA / m or less.
[0074] This is because if the coercive force of the soft magnetic metal powder exceeds 10 kA / m, sufficient magnetic properties may not be obtained.
[0075] The present invention can be produced by a liquid phase reduction method in which a metal salt aqueous solution is reduced with a B-based reducing agent.
[0076] The metal salt is not limited, but an iron salt is preferred.
[0077] Examples of the iron salt include iron (II) sulfate, iron (II) chloride, iron (II) acetate, iron (II) oxalate, iron (III) chloride, and iron (III) sulfate, but are not limited thereto.
[0078] A complexing agent or a reducing agent other than the B-based agent may be added to the aqueous metal salt solution.
[0079] The complexing agent is not particularly limited, and examples thereof include glycine, alanine, ammonium sulfate, ammonium chloride, and trisodium citrate.
[0080] The reducing agent is not particularly limited, and a P-based reducing agent can be used.
[0081] Examples of the P-based reducing agent include sodium hypophosphite and calcium hypophosphite.
[0082] The metal salt aqueous solution is preferably adjusted to pH 6.5 to pH 11.0 using a pH adjuster.
[0083] The pH adjuster is not particularly limited, and examples thereof include sodium hydroxide, aqueous ammonia, and sodium hydrogen carbonate.
[0084] A dispersant, a catalyst, and a defoaming agent may be appropriately added to the aqueous metal salt solution.
[0085] As the reducing agent for reducing the aqueous metal salt solution, a B-based reducing agent is used.
[0086] The B-based reducing agent is not particularly limited, and examples thereof include sodium borohydride, potassium borohydride, and dimethylaminoborane.
[0087] It is also possible to use hydrazine containing no B together with the B-based reducing agent.
[0088] The reduction temperature is preferably 50°C to 95°C.
[0089] This is because when the reduction temperature is lower than 50°C, the amount of B increases, so that α-Fe single-phase particle powder cannot be obtained, and when it is higher than 95°C, the deactivation of the reducing agent becomes rapid, making it difficult to obtain the target soft magnetic metal powder.
[0090] In the present invention, a spheroidization treatment may be performed in order to obtain a soft magnetic metal powder having a desired spheroidization ratio.
[0091] By increasing the spheroidization rate of the soft magnetic metal powder, the filling property into a solvent such as a resin is improved, so that magnetic properties such as magnetic permeability are improved and core loss can be reduced.
[0092] The spheroidization treatment method is not particularly limited, and examples thereof include a mechanochemical treatment that can apply stress such as compaction, shearing, or compression to the particles.
[0093] A mechanical pulverizing device may be used in the mechanochemical treatment in the present invention.
[0094] Examples of the mechanical pulverizing device include a bead mill, a vibration mill, a jet mill, a tower mill, a planetary, rolling, or vibration ball mill, a mechanofusion machine, a mixer, a Henschel mixer, and a homomixer.
[0095] The mechanochemical treatment time is preferably 30 minutes to 180 minutes.
[0096] Example
[0097] The embodiments of the present invention are shown, but the present invention is not limited thereto.
[0098] (Example 1)
[0099] Iron (II) sulfate heptahydrate as an iron salt, glycine as a chelating agent, and sodium hypophosphite as a P-based reducing agent are put into a glass beaker together with 1500 ml of distilled water in such a manner that the concentrations become 0.10 mol / l of iron (II) sulfate heptahydrate, 0.10 mol / l of glycine, and 0.08 mol / l of sodium hypophosphite. The mixture is stirred at room temperature at 100 rpm to 300 rpm using a stirrer while using sodium hydroxide as a pH adjuster to prepare a metal salt aqueous solution of pH 7.0 to pH 8.5.
[0100] Sodium borohydride as a B-based reducing agent was mixed with 300 ml of distilled water to a concentration of 0.28 mol / l, and dissolved by stirring at room temperature at 100 to 300 rpm with a stirrer to prepare a B-based reducing solution.
[0101] The metal salt aqueous solution was heated while being stirred at 100 to 300 rpm by a stirrer in a nitrogen atmosphere, and the B-based reducing solution was added dropwise. The reduction temperature was set to 68°C.
[0102] After the dropwise addition of the B-based reducing solution was completed, the point in time when the foaming of the aqueous metal salt solution disappeared was regarded as the end point of the reduction reaction.
[0103] After the reduction reaction was completed, the mixture was washed with distilled water and replaced with ethanol, and then dried in an inert atmosphere to obtain a soft magnetic metal powder.
[0104] The obtained soft magnetic metal powder was an α-Fe single phase having a spheroidization rate of 68.6%.
[0105] The soft magnetic metal powder was subjected to a mechanochemical treatment for 120 minutes. The mechanochemical treatment was performed to apply shearing force and compressive force to the particles.
[0106] The spheroidization rate of the soft magnetic metal powder of Example 1 subjected to the mechanochemical treatment was 80.2% ( Figure 1 ).
[0107] (Examples 2 to 3, Comparative Examples 1 to 2)
[0108] As described in Table 1, the type and amount of iron salt, the type and amount of complexing agent, the type and amount of reducing agent, the type of pH adjuster, the reduction temperature, the presence or absence of mechanochemical treatment and the time were changed. Otherwise, soft magnetic metal powder was obtained under the same manufacturing conditions as in Example 1.
[0109] (Example 4)
[0110] The soft magnetic metal powder obtained in Example 1, tetraethoxysilane (TEOS), and ammonia water are put into a glass beaker together with 150 ml of isopropyl alcohol in a manner such that the concentrations of the soft magnetic metal powder are 0.30 mol / l, tetraethoxysilane (TEOS), and ammonia water are 0.04 mol / l, respectively, and the TEOS is hydrolyzed for 1 hour at room temperature while being stirred at 100 rpm to 300 rpm by a stirrer to obtain a soft magnetic metal powder coated with silica.
[0111] The silica-coated soft magnetic metal powder was washed with isopropyl alcohol and then dried in a nitrogen atmosphere to obtain a silica-coated soft magnetic metal powder.
[0112] (Comparative Example 3)
[0113] The α-Fe particle powder was synthesized by the polyol method disclosed in Non-Patent Document 1.
[0114] Specifically, 100 ml of ethylene glycol was placed in a glass container equipped with a reflux device, nitrogen gas was blown in at a flow rate of 300 ml / min, and the mixture was stirred at a rotation speed of 100 rpm using a Teflon (registered trademark) stirring blade.
[0115] Into the stirred liquid, ferrous chloride tetrahydrate (FeCl2·4H2O) was added so as to have a concentration of 0.1 mol / l.
[0116] Next, NaOH was added so that the concentration ratio of [OH-] to [Fe] ([OH-] / [Fe]) became 40.
[0117] Next, 2.0×10 hexachloroplatinic acid (IV) was added as a platinum precursor for nucleation. -8 mol / l.
[0118] After the introduction, cooling water was flowed into the reflux vessel, and heating was performed while nitrogen gas was continuously blown in and mechanical stirring was continued. The reduction reaction was performed while reflux was maintained at 170° C. for 20 minutes.
[0119] After the solution was cooled to room temperature, the precipitated particles were transferred into alcohol, washed repeatedly by centrifugal separation, and dried in a nitrogen atmosphere to obtain α-Fe particle powder.
[0120] (Comparative Example 4)
[0121] Carbonyl iron powder (HQ / manufactured by BASF) was used.
[0122] (Average particle size (D), standard deviation of particle size (σ), coefficient of variation (σ / D) and sphericity ratio)
[0123] The images were taken at 2000 to 10000 times magnification using a scanning electron microscope (SEM) (S-4800 FE-SEM, manufactured by Hitachi High-Tech Corporation).
[0124] The longest diameters of all particles within the imaged field of view were measured using image analysis software Image-Analysis (manufactured by Asahi Kasei Engineering Corporation).
[0125] The average particle size, standard deviation of the particle size, coefficient of variation, and sphericity were calculated using the measured size data.
[0126] (Crystal Structure)
[0127] The measurement was performed using an X-ray diffractometer (D8 ADVANCE / manufactured by Bruker Japan Co., Ltd.), and the crystal phase in the sample was identified by Rietveld analysis.
[0128] (Component analysis [Fe, P, Si])
[0129] The measurement was performed using an X-ray fluorescence diffraction apparatus (ZSX PrimusII, manufactured by Rigaku Corporation) in accordance with the "General Rules for X-ray Fluorescence Analysis" of JIS K0119.
[0130] (Component Analysis [B])
[0131] The measurement was performed using an inductively coupled plasma (ICP) emission spectrometer (iCAP6500 / manufactured by Thermo Fisher Scientific).
[0132] (Component Analysis [O])
[0133] The measurement was performed using an oxygen, nitrogen and hydrogen analyzer (EMGA-930 / manufactured by Horiba, Ltd.).
[0134] (magnetic properties)
[0135] The saturation magnetization (σs) and the coercive force (Hc) were measured at an applied magnetic field of 797.7 kA / m using a vibrating sample magnetometer (VSM) (TM-VSM2130MRHL model / manufactured by Tamagawa Seisakusho Co., Ltd.).
[0136] (Viscosity characteristics)
[0137] 0.5 ml of castor oil and 3.2 g of clear varnish were added to 5.0 g of the soft magnetic metal powder in Examples and Comparative Examples, and stirred at 1500 rpm for 3 minutes using a rotation / revolution mixer (Degassing Rentaro ARE-310, manufactured by THINKY Co., Ltd.) to prepare slurry.
[0138] The viscosity of the prepared slurry was measured at 25° C. and a rotation speed of 20 rpm using an E-type viscometer (TVE-35 Type H, H3°×R9.7 cone / manufactured by Toki Sangyo Co., Ltd.).
[0139] (Maximum height of thin layer: Rmax)
[0140] To 5.0 g of the soft magnetic metal powder in the examples and comparative examples, 0.5 ml of castor oil and 3.2 g of clear lacquer were added, and the mixture was stirred at 1500 rpm for 3 minutes using a rotation / revolution mixer to prepare a slurry.
[0141] The prepared slurry was applied onto a PET film using a 3-mill applicator and dried at room temperature to form a thin layer (coated film) having a film thickness of about 20 μm.
[0142] The maximum height Rmax of the thin layer was measured using a non-contact surface roughness measuring instrument (NewView600, manufactured by Canon Marketing Japan, Ltd.).
[0143] Table 1 shows the materials and conditions used in Examples and Comparative Examples, and Table 2 shows the results.
[0144] [Table 1]
[0145]
[0146] [Table 2]
[0147]
[0148] Table 2 shows that the soft magnetic metal powder of the present invention has a high spheroidization rate, is an aggregate of fine particles with a narrow particle size distribution, has a high saturation magnetization, has a low viscosity of the slurry and is easy to form a thin layer, and the formed thin layer has excellent surface smoothness.
[0149] Industrial Applicability
[0150] The soft magnetic metal powder in the present invention is an aggregate of fine particles. Since it has a high sphericity, it can be used to make a slurry with low viscosity. Since it contains a small amount of boron that reduces saturation magnetization, it can be used to make electronic parts with excellent magnetic properties. Moreover, since the particle size distribution is narrow, it has high solvent dispersibility and can form a thin layer with excellent surface smoothness.
[0151] Therefore, the present invention has high industrial applicability.
Claims
1. A soft magnetic metal powder having an average particle size of 0.05 μm or more and 1.5 μm or less, a coefficient of variation expressed by the following formula 1 of 0.25 or less, a boron content of less than 1.5 wt % excluding 0, and a spheroidization rate expressed by the following formula 2 of 75% or more, Formula 1: Standard deviation of particle size / average particle size, Formula 2: (area / area of the smallest circumscribed circle)×100.
2. The soft magnetic metal powder according to claim 1, wherein The amount of oxygen is 3.0 wt% or less.
3. The soft magnetic metal powder according to claim 1 or 2, wherein: The iron content is 93% by weight or more.
4. The soft magnetic metal powder according to claim 1 or 2, wherein The soft magnetic metal powder is coated with one or more metal oxides.
5. The soft magnetic metal powder according to claim 4, wherein The metal element of the metal oxide is aluminum, silicon, zirconium, titanium, yttrium or phosphorus.
6. A method for producing the soft magnetic metal powder according to claim 1 or 2, wherein: The soft magnetic metal powder is obtained by spheroidizing the soft magnetic metal powder produced by a liquid phase reduction method, wherein a reducing agent containing a boron reducing agent is dropped into a metal salt aqueous solution containing a metal salt, a complexing agent, a pH adjusting agent, and a phosphorus reducing agent.
7. A method for producing the soft magnetic metal powder according to claim 1 or 2, wherein: The soft magnetic metal powder is obtained by spheroidizing the soft magnetic metal powder through mechanochemical treatment.
Citation Information
Patent Citations
Amorphous soft magnetic alloy powder, dust core and inductor
JP2010261065A